The United States in decline - Lachmann, Richard (Bingley, U.K. : Emerald, 2014)
The essays in this volume examine finance, industry and strategy both internally and on a global scale. Contributors clarify our understanding of the current state and future trajectory of the United States and the effect of decline on its citizens and the world.
Introduction : the United States in decline? / Richard Lachmann -- Can the U.S. sustain its global position? Dynamism and stagnation in the U.S. institutional model / Fred Block, Matthew R. Keller -- Cold War and China in the (un)making of the dollar standard / Ho-fung Hung -- Capital accumulation and the rise of Finance / Marcel Knudsen -- The flailing hegemon : managing U.S. military decline / Ian Roxborough, Zoe Levy -- Elite fragmentation and the decline of the United States / Mark Mizruchi, Mikell Hyman -- From consensus to paralysis in the United States, 1960-2010 / Richard Lachmann -- Convergence-2, or the fate of other superpower / Georgi Derluguian.
Includes index.
Print version record
Keywords: Political Science -- History & Theory; Political science & theory; Geopolitics; Social theory; United States -- History -- 20th century; United States -- History -- 21st century; United States -- Politics and government -- 20th century; United States -- Politics and government -- 2001-2009.